(untitled) (The Research of Medical Science Review, 2024)
To identify and analyze the type and severity of hearing loss effects of chemotherapy on the auditory system of patients within age limit of 7-56 years with cancer treated with cisplatin and carboplatin, assessed through standardized audiological procedures, Is to find out the type and severity of hearing impairment among chemotherapeutic patients, The study design will be analytic cross-sectional study the data will collect from the University of Lahore. Sample size was calculated based on prevalence (36.5%) of Prevalence of type and severity of hearing impairment among chemotherapeutic patients. The sample size was calculated 139 through online sample size calculator. nonprobability purposive sampling technique. Inclusion Criteria patients with age 7 to 56 year’s will be included in this study and Exclusion Criteria Children with co morbidities which can result in hearing loss. Demographic Performa will be given to all caregivers of participants tocollect data. Data will be collected from children hospital Lahore. After the Permission of higher Authorities of children hospital. After taking the written consent from the child or their family members, their hearing will be assessed to check the severity levels and its types of hearing loss. The ears was checked by otoscope, tympanometry and assessed with standard pure tone audiometer, The total of 137 patients compromised the study populations. The degree of hearing loss is often related the dose. Audiogram finding shows that In which 55.5%(n=76) patients were had normal hearing level received a cisplatin dose 100mg/m2in while45.5%(n=61) patients were had impaired hearing loss received a cisplatin dose 400mg/m2 in which 26.3%(n=36) patients were had a mild SNHL,15.3%(n=21)patients mild to moderate SNHL,2.9%(n=4)patients moderately severe SNHL, tympanometry finding shows that 105 patients were had type A tympanogram and 32 patients were had type B tympanogram, This study concluded that the prevalence of type and severity of hearing impairment is so high chemotherapeutic patients.